Dietary Selenium Intake and Type-2 Diabetes: A Cross-Sectional Population-Based Study on CUME Project - Dias, João Pedro Viana; Costa Sobrinho, Paulo de Souza; Pimenta, Adriano Marçal; Hermsdorff, Helen Hermana Miranda; Bressan, Josefina; Nobre, Luciana Neri (Frontiers in Nutrition, 2021)
Background and Aim: Previous studies have suggested that the specific association between Selenium (Se) and diabetes remains unclear. The present study aimed to investigate the association between dietary Se and type 2 diabetes (T2D) in the Brazilian cohort (Cohort of Universities of Minas Gerais - CUME). Methods and Results: this cross-sectional study was conducted on a large sample comprising 4,106 participants of CUME project, which is an open concurrent cohort restricted to a high educational-level population group, constituted of graduates in federal institutions of higher education located in the State of Minas Gerais, Brazil. Information about socioeconomic characteristics, anthropometric measures, and dietary were collected from each subject for analysis. We classified the sample into energy-adjusted tertiles of dietary Se intake (µg/d). Differences in the continuous data were evaluated by Kruskal-Wallis H-test (abnormal data); the χ2 test assessed differences in qualitative data. The average Se intake was 165.12 μg/day, and the prevalence of T2D 2.8% in the studied population. The average age was 36 years, 1,209 male, and 2,807 female. Significant differences were observed across all tertiles of Se intake in terms of age, sex, activity level, alcohol intake, energy intake, sugar, carbohydrates, lipids, fiber, energy-adjusted meats intake. However, not significant differences were observed across all tertiles of Se intake in terms of BMI, smoking status, and type 2 diabetes. The results indicated that there was no significant association between dietary Se intake and the prevalence of T2D. Conclusion: Dietary Se intake was not associated with prevalence of T2D, despite high intake of this micronutrient in this sample. These results contradict studies that identified association between Se intake and T2D, with values of Se intake much lower than observed in this study. So, it seems that this relationship remains controversial.